Prevalence and Precipitating Factors of Migraine in Secondary School Students in Thailand - Saengow, Vitchayaporn Emarach; Tangcheewinsirikul, Sirikarn (Journal of Child Science, 2018)
Introduction Migraine is the most common primary headache in children which leads to disturbance of school performance and impaired quality of life. The prevalence of migraine is different between countries and ethnicities; this study determines the prevalence and precipitating factors of migraine in Thailand.Method This cross-sectional school-based study was conducted in Nakhon Ratchasima. The children aged between 12 and 18 years from four secondary schools were selected by stratified randomization method. The screening questionnaire and directed interview with physical examination were done and migraine was diagnosed based on the criteria of International Classification of Headache Disorders III. The prevalence of migraine was identified and baseline characteristic of disease with precipitating factors was evaluated.Results A total of 2,744 students aged between 12 and 18 years (900 males, 1,844 females) were recruited; mean age was 14.3 ± 1.75 years. Fifty-five students were diagnosed with migraine (20 males [36.36%], 35 females [63.64%], mean age: 15.1 ± 1.6 years). The prevalence of migraine was 1.98%. Migraine prevalence was predominant in female adolescents with a common feature being migraine without aura. The important precipitating factor in this study was stress from academic achievement.Conclusion Migraine is a common disease in children and under-recognized in school students, and stress is the major precipitating factor.
Keywords: migraine; prevalence; pediatric; students; severity; precipitating factors